Delay-Dependent Stability Criterion of Caputo Fractional Neural Networks with Distributed Delay - Abdulaziz Alofi; Jinde Cao; Ahmed Elaiw; Abdullah Al-Mazrooei (Discrete Dynamics in Nature and Society)
This paper is concerned with the finite-time stability of Caputo fractional neural networks with distributed delay. The factors of such systems including Caputo’s fractional derivative and distributed delay are taken into account synchronously. For the Caputo fractional neural network model, a finite-time stability criterion is established by using the theory of fractional calculus and generalized Gronwall-Bellman inequality approach. Both the proposed criterion and an illustrative example show that the stability performance of Caputo fractional distributed delay neural networks is dependent on the time delay and the order of Caputo’s fractional derivative over a finite time.